K2-140b – an eccentric 6.57 d transiting hot Jupiter in Virgo. Issue 2 (5th January 2018) - Giles, H A C; Bayliss, D; Espinoza, N; Brahm, R; Blanco-Cuaresma, S; Shporer, A; Armstrong, D; Lovis, C; Udry, S; Bouchy, F; Marmier, M; Jordán, A; et al.
Abstract: We present the discovery of K2-140b, a P = 6.57 d Jupiter-mass ( MP = 1.019 ± 0.070MJup ) planet transiting a V = 12.5 (G5-spectral type) star in an eccentric orbit (e = 0.120^+0.056_-0.046 ) detected using a combination of K2 photometry and ground-based observations. With a radius of 1.095 ± 0.018 RJup, the planet has a bulk density of 0.726 ± 0.062 ρJup . The host star has a [Fe/H] of 0.12 ± 0.045, and from the K2 light curve, we find a rotation period for the star of 16.3 ± 0.1 d. This discovery is the 9th hot Jupiter from K2 and highlights K2 's ability to detect transiting giant planets at periods slightly longer than traditional, ground-based surveys. This planet is slightly inflated, but much less than others with similar incident fluxes. These are of interest for investigating the inflation mechanism of hot Jupiters.